2018
DOI: 10.1177/0739456x18772074
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward a Shared Understanding of the U.S. Shrinking City

Abstract: Scholarly work on “shrinking” cities grew following the 2010 census, resulting in a diverse body of popular and academic literature. However, this has not produced a widely accepted definition of the “shrinking city.” We analyze definitions used in a sample of papers on U.S. shrinking cities and propose an empirically justified definition that reflects the shrinking cities research agenda and is easily operationalized. We demonstrate that our resulting universe of eighty cities represents the places studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…Severely depopulating cities have recently been referred to as 'shrinking cities (Newman et al, 2016a).' Several journal articles published between 2002 and 2014 revealed that 73 U.S. cities were identified as shrinking (Ganning and Tighe, 2015). While cities such as Cleveland and Detroit sometimes serve as the posterchilds of shrinkage, as of 2007, 370 cities throughout the world with populations over 100,000 shrunk by at least 10% over the last 50 years (Oswalt and Rieniets, 2007).…”
Section: Literature Review 21 Urban Decline and Housing Abandonmentmentioning
confidence: 99%
“…Severely depopulating cities have recently been referred to as 'shrinking cities (Newman et al, 2016a).' Several journal articles published between 2002 and 2014 revealed that 73 U.S. cities were identified as shrinking (Ganning and Tighe, 2015). While cities such as Cleveland and Detroit sometimes serve as the posterchilds of shrinkage, as of 2007, 370 cities throughout the world with populations over 100,000 shrunk by at least 10% over the last 50 years (Oswalt and Rieniets, 2007).…”
Section: Literature Review 21 Urban Decline and Housing Abandonmentmentioning
confidence: 99%
“…Many urban areas around the world currently experience various challenging and interdependent social, environmental, and economic sustainability problems, which vary substantially between contexts. For example, some experience rapid population increases (fueled sometimes by migration) or rapid population declines, ageing societies, urban decay, and environmental pollution [1][2][3][4][5][6][7]. These contemporary urban challenges are reflected in numerous scientific studies [8][9][10], as well as in the UN and EU policy agendas.…”
Section: Introductionmentioning
confidence: 99%
“…Like definitions and goals in the literature, there are also different ways that the causes of shrinkage are considered. They often differ according to the geography they are describing, but little has been written that uniquely categorizes these different traditions of shrinkage; apart from somewhat distinct scholarly traditions worldwide, places in countries as different as Japan, Germany, and the United States can all be described as “shrinking cities.” The structural collapse of industrial economies in both Germany and the United States are often cited as causes of shrinkage, whereas literature on shrinking Japanese cities tends to focus on low birth rate (Ganning and Tighe 2018; Grant et al 2006; Beyer, Hagemann, and Rieniets 2006). Pallagst, Wiechmann, and Martinez-Fernandez (2013) state that “Marked by a loss of employment opportunities and the attendant out-migration of population, many shrinking cities have suffered from the post-industrial shift from manufacturing to service industries” (p. 3).…”
Section: Defining the Shrinking Citymentioning
confidence: 99%
“…The fragmented nature with which shrinking cities have been described has received some criticism (Bernt 2016; Oswalt 2005; LaCroix 2010; Ganning and Tighe 2018). Oswalt (2005) points to a degree of superficiality, calling it “a problematic term” due to the multitude of causes that are said to be united under symptoms of population loss and economic decline (p. 12).…”
Section: Defining the Shrinking Citymentioning
confidence: 99%
See 1 more Smart Citation